Tracking population structure and phenology through time using ancient genomes from waterlogged white oak wood - Stefanie Wagner; Andaine Seguin‐Orlando; Jean‐Charles Leplé; Thibault Leroy; Céline Lalanne; Karine Labadie; Jean‐Marc Aury; Sandy Poirier; Patrick Wincker; Christophe Plomion; Antoine Kremer; Ludovic Orlando (Molecular Ecology, 2024)
Whole genome characterizations of crop plants based on ancient DNA have provided unique keys for a better understanding of the evolutionary origins of modern cultivars, the pace and mode of selection underlying their adaptation to new environments and the production of phenotypes of interest. Although forests are among the most biologically rich ecosystems on earth and represent a fundamental resource for human societies, no ancient genome sequences have been generated for trees. This contrasts with the generation of multiple ancient reference genomes for important crops. Here, we sequenced the first ancient tree genomes using two white oak wood remains from Germany dating to the Last Little Ice Age (15th century CE, 7.3× and 4.0×) and one from France dating to the Bronze Age (1700 BCE, 3.4×). We assessed the underlying species and identified one medieval remains as a hybrid between two common oak species ( Quercus robur and Q. petraea ) and the other two remains as Q. robur . We found that diversity at the global genome level had not changed over time. However, exploratory analyses suggested that a reduction of diversity took place at different time periods. Finally, we determined the timing of leaf unfolding for ancient trees for the first time. The study extends the application of ancient wood beyond the classical proxies of dendroclimatology, dendrochronology, dendroarchaeology and dendroecology, thereby enhancing resolution of inferences on the responses of forest ecosystems to past environmental changes, epidemics and silvicultural practices.